A hydrogen evolution catalytic electrode and its preparation method and application
By using the reaction of nickel foam matrix with cobalt nickel salt and sodium hypophosphite in electrolytic hydrogen production technology, calcination and high-temperature phosphating treatment, cobalt nickel phosphorus alloy catalytic electrode is prepared, which solves the high cost and corrosion resistance of precious metal catalysts. The problem of insufficient results has achieved efficient and stable electrolytic hydrogen production effect.
Patent Information
- Application Number
- CN202211013633.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-08-23
AI Technical Summary
In the existing electrolytic hydrogen production technology, precious metal catalysts are costly and easily corrosive, and the activity and corrosion resistance of non-precious metal catalysts are insufficient, which limits the industrial development of electrolytic hydrogen production.
A foam nickel matrix is used to react in a mixed solution containing cobalt salt, nickel salt and sodium hypophosphite. After calcination and high-temperature phosphating treatment, a cobalt nickel phosphorus alloy catalytic electrode is prepared to improve its conductivity and corrosion resistance.
The prepared nano-scale strand spherical cobalt-nickel-phosphorus alloy catalytic electrode exhibits excellent stability and efficient catalytic activity in an alkaline environment, reducing the overpotential of hydrogen production by electrolyzing water, and improving the conductivity and corrosion resistance of the material.
Smart Images

Figure CN115233252B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen evolution catalysts for electrolysis of water, and in particular to a hydrogen evolution catalytic electrode and a preparation method and application thereof. Background Art
[0002] As human demand for energy continues to grow, traditional energy shortages and environmental problems become increasingly prominent, hydrogen energy, as a green and clean energy with high calorific value and storability, has gradually come into people's view and application. Traditional methods of producing hydrogen from fossil fuels and industrial byproducts have high carbon emissions, and water electrolysis is considered to be the most promising method of producing hydrogen.
[0003] At present, the energy consumption of water electrolysis for hydrogen production is high, and the economic cost seriously restricts its industrial development. Therefore, reducing the actual decomposition voltage of water electrolysis and improving the electrolysis efficiency by using efficient hydrogen evolution electrocatalysts are the key to the development of water electrolysis for hydrogen production technology. The commercialized Pt-based electrodes have the best hydrogen evolution reaction (HER) activity, but precious metals are not only expensive but also scarce in earth reserves. Therefore, the research and development of non-precious metal efficient hydrogen evolution catalysts is particularly important for water electrolysis for hydrogen production technology.
[0004] Transition metals such as nickel and cobalt have low hydrogen adsorption free energy, and the metal synergy between transition metals can enhance HER activity. The conductivity and corrosion resistance of transition metal phosphides are improved, and they are also receiving much research attention. The chemical plating preparation method is simple and low-cost, but the obtained nickel-cobalt-phosphorus material is amorphous, and the catalyst is easily corroded when electrolyzing water to produce hydrogen in an alkaline environment, and the activity time is short. Therefore, designing a simple preparation method and microcrystallized cobalt-nickel alloy phosphide catalytic electrode to improve the hydrogen evolution activity of the catalyst is of great significance to industrial production in this field. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a hydrogen evolution catalytic electrode and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a hydrogen evolution catalytic electrode, comprising the following steps:
[0008] (1) placing a foamed nickel substrate in a mixed solution containing a cobalt salt, a nickel salt, sodium hypophosphite and a complexing agent to react to obtain a cobalt-nickel-phosphorus alloy material;
[0009] (2) calcining the cobalt-nickel-phosphorus alloy material in an inert atmosphere to obtain a calcined cobalt-nickel-phosphorus alloy material;
[0010] (3) The calcined cobalt-nickel-phosphorus alloy material and the phosphorus source are heated in an inert atmosphere to obtain the hydrogen evolution catalytic electrode.
[0011] Preferably, the cobalt salt in step (1) is CoSO4, CoSO4·7H2O, Co(NO3)2, Co(NO3)2·6H2O, CoCl2 or CoCl2·6H2O, the nickel salt is NiSO4, NiSO4·6H2O, Ni(NO3)2, Ni(NO3)2·6H2O, NiCl2 or NiCl2·6H2O, and the complexing agent is sodium citrate and boric acid.
[0012] Preferably, the molar ratio of the cobalt salt to the nickel salt in step (1) is 0.5 to 9:1;
[0013] The solvent in the mixed solution is water, and the mass concentration of the cobalt salt in the mixed solution is 10-60 g / L;
[0014] The mass ratio of the cobalt salt, sodium hypophosphite and complexing agent is 1.5-3.5:0.5-1.5:2.5-3.5;
[0015] The mass ratio of the cobalt salt to the nickel foam matrix is 25:0.5-2.5;
[0016] The mass ratio of sodium citrate to boric acid in the complexing agent is 1.5-2.5:1.
[0017] Preferably, the reaction temperature in step (1) is 50 to 90° C., and the reaction time is 10 to 250 min.
[0018] Preferably, the calcination temperature in step (2) is 400-800° C., and the calcination time is 1-3 hours.
[0019] Preferably, the phosphorus source in step (3) is sodium hypophosphite or phosphorus powder.
[0020] Preferably, in step (3), the mass ratio of the calcined cobalt-nickel-phosphorus alloy material to the phosphorus source is 0.8-1.2:0.8-1.2.
[0021] Preferably, the target temperature of the heating in step (3) is 300-550° C., and the holding time is 30-210 min.
[0022] The heating rate from room temperature to the intermediate temperature is 1-10°C / min, the intermediate temperature is 70-90°C, the insulation time after reaching the intermediate temperature is 30-50min, and the heating rate from the intermediate temperature to the target temperature is 1-10°C / min.
[0023] The invention also provides a hydrogen evolution catalytic electrode obtained by the preparation method.
[0024] The present invention also provides the use of the hydrogen evolution catalytic electrode in a hydrogen evolution catalyst for water electrolysis.
[0025] The beneficial effects of the present invention are:
[0026] (1) The present invention provides a method for preparing a hydrogen evolution catalytic electrode, wherein a foamed nickel substrate is placed in a mixed solution containing a cobalt salt, a nickel salt, sodium hypophosphite and a complexing agent, and a cobalt-nickel-phosphorus alloy material is obtained by reaction; the cobalt-nickel-phosphorus alloy material is calcined to obtain a calcined cobalt-nickel-phosphorus alloy material; the calcined cobalt-nickel-phosphorus alloy material is heated with a phosphorus source to obtain the hydrogen evolution catalytic electrode. In the present invention, the cobalt salt and the nickel salt are reduced to the surface of the foamed nickel substrate by the reduction action of sodium hypophosphite, and phosphorus atoms are doped by high-temperature calcination and phosphating to improve the material structure and enhance the material performance. The preparation method of the present invention has low economic cost, a simple and easy-to-operate preparation process, and further introduces phosphorus elements on the basis of the cobalt-nickel-phosphorus alloy by high-temperature phosphating to improve the conductivity and corrosion resistance of the material.
[0027] (2) The hydrogen evolution catalytic electrode provided by the present invention is a nano-scale chain ball-shaped particle with stable structure and performance, which reduces the electronic conduction barrier in the alkaline water electrolysis process, makes the material transition from amorphous to crystalline, further improves the electronic conductivity, and improves the corrosion resistance of the material to alkaline solution; it has excellent hydrogen evolution effect, reduces the overpotential in water electrolysis, and has good stability. It is easy to store and has good hydrogen evolution catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope characterization image of the hydrogen evolution catalytic electrode prepared in Example 1;
[0029] Figure 2 This is the polarization curve of the hydrogen evolution catalytic electrode prepared in Example 1 in an alkaline environment. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a hydrogen evolution catalytic electrode, comprising the following steps:
[0031] (1) placing a foamed nickel substrate in a mixed solution containing a cobalt salt, a nickel salt, sodium hypophosphite and a complexing agent to react to obtain a cobalt-nickel-phosphorus alloy material;
[0032] (2) calcining the cobalt-nickel-phosphorus alloy material in an inert atmosphere to obtain a calcined cobalt-nickel-phosphorus alloy material;
[0033] (3) The calcined cobalt-nickel-phosphorus alloy material and the phosphorus source are heated in an inert atmosphere to obtain the hydrogen evolution catalytic electrode.
[0034] In the present invention, the nickel foam substrate is subjected to a pretreatment process before use; the pretreatment is to place the nickel foam substrate in acetone and anhydrous ethanol solutions for ultrasonic treatment in sequence, and then place it in a weak acid for activation.
[0035] In the present invention, the frequency of ultrasonic treatment of the foamed nickel substrate in acetone solution is preferably 10-60kHz, further preferably 30-50kHz, and more preferably 40kHz; the time of ultrasonic treatment of the foamed nickel substrate in acetone solution is preferably 20-40min, further preferably 25-35min, and more preferably 30min; the frequency of ultrasonic treatment of the foamed nickel substrate in anhydrous ethanol solution is preferably 10-60kHz, further preferably 30-50kHz, and more preferably 40kHz; the time of ultrasonic treatment of the foamed nickel substrate in anhydrous ethanol solution is preferably 20-40min, further preferably 25-35min, and more preferably 30min; the activation time of the foamed nickel substrate in weak acid is preferably 1-10min, further preferably 3-7min, and more preferably 4-6min; the weak acid is preferably H2SO4, and the mass concentration of the weak acid is preferably 15-20g / L, further preferably 16-19g / L, and more preferably 17-18g / L.
[0036] In the present invention, the cobalt salt in step (1) is preferably CoSO4, CoSO4·7H2O, Co(NO3)2, Co(NO3)2·6H2O, CoCl2 or CoCl2·6H2O; the nickel salt is preferably NiSO4, NiSO4·6H2O, Ni(NO3)2, Ni(NO3)2·6H2O, NiCl2 or NiCl2·6H2O; and the complexing agent is preferably sodium citrate and boric acid.
[0037] In the present invention, the sodium hypophosphite in step (1) is used as a reducing agent in the mixed solution, thereby ensuring the smooth preparation of the cobalt-nickel-phosphorus alloy material.
[0038] In the present invention, the molar ratio of the cobalt salt to the nickel salt in step (1) is preferably 0.5 to 9:1, more preferably 2 to 7:1, and even more preferably 4 to 5:1.
[0039] In the present invention, the solvent in the mixed solution is preferably water, and the mass concentration of the cobalt salt in the mixed solution is preferably 10 to 60 g / L, more preferably 20 to 50 g / L, and even more preferably 30 to 40 g / L.
[0040] In the present invention, the mass ratio of the cobalt salt, sodium hypophosphite and complexing agent is preferably 1.5-3.5: 0.5-1.5: 2.5-3.5, more preferably 2-3: 0.8-1.2: 2.8-3.2, and more preferably 2.5: 1: 3.
[0041] In the present invention, the mass ratio of the cobalt salt to the nickel foam matrix is preferably 25:0.5-2.5, more preferably 25:0.8-1.5, and more preferably 25:1-1.2;
[0042] In the present invention, the mass ratio of sodium citrate to boric acid in the complexing agent is preferably 1.5 to 2.5:1, more preferably 1.8 to 2.2:1, and more preferably 2:1.
[0043] In the present invention, the reaction temperature in step (1) is preferably 50-90°C, more preferably 60-80°C, and more preferably 70°C; the reaction time is preferably 10-250 min, more preferably 60-200 min, and more preferably 100-160 min.
[0044] In the present invention, after the reaction in step (1) is completed, the product system is washed with water and ethanol in sequence, and the number of times of washing with water and ethanol is preferably greater than or equal to 4 times, more preferably greater than or equal to 5 times, and more preferably greater than or equal to 6 times; after washing, drying is performed; the drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 60°C, and the drying time is preferably 5-7h, more preferably 5.5-6.5h, and more preferably 6h; after drying, a cobalt-nickel-phosphorus alloy material is obtained.
[0045] In the present invention, the inert gas in step (2) is preferably nitrogen, helium, neon or argon.
[0046] In the present invention, the calcination in step (2) is carried out in a porcelain boat; the calcination temperature is preferably 400-800°C, more preferably 500-700°C, and more preferably 600°C; the calcination time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h.
[0047] In the present invention, the phosphorus source in step (3) is preferably sodium hypophosphite or phosphorus powder, more preferably sodium hypophosphite.
[0048] In the present invention, the mass ratio of the calcined cobalt-nickel-phosphorus alloy material to the phosphorus source in step (3) is preferably 0.8-1.2:0.8-1.2, more preferably 0.9-1.1:0.9-1.1, and more preferably 1:1.
[0049] In the present invention, the heating in step (3) is performed in a tube furnace, and the inert atmosphere is preferably helium, neon or argon; the target temperature of the heating is preferably 300 to 550° C., more preferably 350 to 500° C., and more preferably 400 to 450° C.; the holding time is preferably 30 to 210 min, more preferably 50 to 190 min, and more preferably 100 to 140 min;
[0050] In the present invention, the heating rate from room temperature to the intermediate temperature is preferably 1-10°C / min, more preferably 3-8°C / min, and more preferably 5°C / min; the intermediate temperature is preferably 70-90°C, more preferably 75-85°C, and more preferably 80°C; the insulation time after heating to the intermediate temperature is preferably 30-50min, more preferably 35-45min, and more preferably 40min; the heating rate from the intermediate temperature to the target temperature is preferably 1-10°C / min, more preferably 3-8°C / min, and more preferably 5-6°C / min.
[0051] In the present invention, after the heating is completed, the sample is naturally cooled to room temperature and then taken out to obtain the hydrogen evolution catalytic electrode.
[0052] The invention also provides a hydrogen evolution catalytic electrode obtained by the preparation method.
[0053] The present invention also provides the use of the hydrogen evolution catalytic electrode in a hydrogen evolution catalyst for water electrolysis.
[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0055] Example 1
[0056] The nickel foam substrate was placed in an acetone solution and ultrasonically treated at 40kHz for 30min, then placed in an anhydrous ethanol solution and ultrasonically treated at a frequency of 40kHz for 30min, and then placed in 16g / L sulfuric acid for activation for 3min. 1.2g of the treated substrate was placed in a mixed solution of 30g of cobalt sulfate heptahydrate, 5g of nickel sulfate hexahydrate, 20g of sodium citrate, 10g of boric acid, 10g of sodium hypophosphite and 1000mL of deionized water, and reacted at 60°C for 200min. The product was washed with water for 4 times, and then washed with ethanol for 4 times. After the washing, it was dried at 60°C for 6h to obtain a nickel-cobalt-phosphorus alloy material; the nickel-cobalt-phosphorus alloy material was placed in a porcelain boat, and calcined at 400°C for 3h under argon protection, 1g of the calcined material and 1g of sodium hypophosphite were placed in a tubular furnace, and in an argon atmosphere, they were first heated to 80°C at a heating rate of 5°C / min and kept warm for 40min, and then heated to 300°C at a heating rate of 5°C / min and kept warm for 200min, and then cooled to room temperature to obtain a hydrogen evolution catalytic electrode.
[0057] The hydrogen evolution catalytic electrode prepared in this example was characterized by scanning electron microscopy, and the results are as follows: Figure 1 As shown in the figure, it can be observed that the hydrogen evolution catalytic electrode prepared in this embodiment is a nano-scale chain ball-shaped particle; the hydrogen evolution catalytic electrode prepared in this embodiment is placed in an alkaline environment, and a linear sweep voltammetry test is performed under a three-electrode system. The results are as follows Figure 2 As shown in the figure, it can be observed that the hydrogen evolution catalyst electrode prepared in this embodiment has a -2 At a current density of -120 mV, the overpotential is -120 mV.
[0058] Example 2
[0059] The nickel foam substrate was placed in an acetone solution and ultrasonically treated at 30kHz for 35min, then placed in an anhydrous ethanol solution and ultrasonically treated at a frequency of 30kHz for 35min, and then placed in 17g / L sulfuric acid for activation for 2min. 1.6g of the treated substrate was placed in a mixed solution of 20g of cobalt sulfate heptahydrate, 15g of nickel sulfate hexahydrate, 22g of sodium citrate, 10g of boric acid, 12g of sodium hypophosphite and 1000mL of deionized water, and reacted at 65°C for 170min. The product was washed with water 5 times and then washed with ethanol 5 times. After washing, the mixture was dried at 55°C for 6.5h to obtain a nickel-cobalt-phosphorus alloy material; the nickel-cobalt-phosphorus alloy material was placed in a porcelain boat and calcined at 500°C for 2.5h under argon protection; 1g of the calcined material and 0.8g of sodium hypophosphite were placed in a tubular furnace, and heated to 70°C at a heating rate of 6°C / min and kept warm for 50min under an argon atmosphere, and then heated to 450°C at a heating rate of 6°C / min and kept warm for 160min, and then cooled to room temperature to obtain a hydrogen evolution catalytic electrode.
[0060] The test method consistent with that in Example 1 was used to obtain the hydrogen evolution catalyst electrode prepared in this example at 10 mA·cm -2 At a current density of -123 mV, the overpotential is -123 mV.
[0061] Example 3
[0062] The nickel foam substrate was placed in an acetone solution and ultrasonically treated at 50kHz for 25min, then placed in an anhydrous ethanol solution and ultrasonically treated at a frequency of 50kHz for 25min, and then placed in 18g / L sulfuric acid for activation for 4min. 1.5g of the treated substrate was placed in a mixed solution of 25g of cobalt sulfate heptahydrate, 8g of nickel sulfate hexahydrate, 18g of sodium citrate, 10g of boric acid, 10g of sodium hypophosphite and 1000mL of deionized water, and reacted at 70°C for 160min. The product was washed with water 6 times. Then it was washed with ethanol for 4 times and dried at 65°C for 5.5h to obtain a nickel-cobalt-phosphorus alloy material. The nickel-cobalt-phosphorus alloy material was placed in a porcelain boat and calcined at 600°C for 2h under argon protection. 1g of the calcined material and 1.2g of sodium hypophosphite were placed in a tubular furnace and heated to 75°C at a heating rate of 4°C / min for 45min under an argon atmosphere, and then heated to 500°C at a heating rate of 4°C / min for 120min, and then cooled to room temperature to obtain a hydrogen evolution catalytic electrode.
[0063] The test method consistent with that in Example 1 was used to obtain the hydrogen evolution catalyst electrode prepared in this example at 10 mA·cm -2 At a current density of -118 mV, the overpotential is -118 mV.
[0064] It can be seen from the above embodiments that the preparation method provided by the present invention has low economic cost, a simple preparation process and is easy to operate, and the conductivity and corrosion resistance of the material are improved by further introducing phosphorus element on the basis of cobalt-nickel-phosphorus alloy through high-temperature phosphating. The prepared hydrogen evolution catalytic electrode is a nano-scale chain ball-shaped particle with stable structure and performance, excellent corrosion resistance in an alkaline environment, easy to store, and good hydrogen evolution catalytic activity.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogen evolution catalytic electrode, characterized in that: It includes the following steps: (1) placing a foamed nickel substrate in a mixed solution containing a cobalt salt, a nickel salt, sodium hypophosphite and a complexing agent to react to obtain a cobalt-nickel-phosphorus alloy material; (2) calcining the cobalt-nickel-phosphorus alloy material in an inert atmosphere to obtain a calcined cobalt-nickel-phosphorus alloy material; (3) heating the calcined cobalt-nickel-phosphorus alloy material and a phosphorus source in an inert atmosphere to obtain the hydrogen evolution catalytic electrode; The molar ratio of the cobalt salt to the nickel salt in step (1) is 2 to 9:1; The solvent in the mixed solution is water, and the mass concentration of the cobalt salt in the mixed solution is 20-60 g / L; The mass ratio of the cobalt salt, sodium hypophosphite and complexing agent is 1.5-3.5:0.5-1.5:2.5-3.5; The calcination temperature in step (2) is 500-800° C. and the calcination time is 2-3 hours; The mass ratio of the calcined cobalt-nickel-phosphorus alloy material to the phosphorus source in step (3) is 0.8-1.2:0.8-1.2; The target temperature of the heating in step (3) is 450-550°C.
2. The preparation method according to claim 1, characterized in that The cobalt salt in step (1) is CoSO4, CoSO4·7H2O, Co(NO3)2, Co(NO3)2·6H2O, CoCl2 or CoCl2·6H2O, the nickel salt is NiSO4, NiSO4·6H2O, Ni(NO3)2, Ni(NO3)2·6H2O, NiCl2 or NiCl2·6H2O, and the complexing agent is sodium citrate and boric acid.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the cobalt salt to the nickel foam matrix in step (1) is 25:0.5-2.5; The mass ratio of sodium citrate to boric acid in the complexing agent is 1.5-2.5:
1.
4. The preparation method according to claim 3, characterized in that: The reaction temperature of step (1) is 50-90° C., and the reaction time is 10-250 min.
5. The preparation method according to claim 1, characterized in that: The phosphorus source in step (3) is sodium hypophosphite or phosphorus powder.
6. The preparation method according to claim 5, characterized in that: The holding time after heating to the target temperature in step (3) is 30 to 210 minutes; The heating rate from room temperature to the intermediate temperature is 1-10°C / min, the intermediate temperature is 70-90°C, the insulation time after reaching the intermediate temperature is 30-50min, and the heating rate from the intermediate temperature to the target temperature is 1-10°C / min.
7. A hydrogen evolution catalytic electrode obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the hydrogen evolution catalytic electrode according to claim 7 in a hydrogen evolution catalyst for water electrolysis.